A Decade of Manpower Training and Development - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "A Decade of Manpower Training and Development" by Garth L. Mangum and John Walsh.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z